Expression of pro-inflammatory cytokines in Atlantic salmon (Salmo salar) after intraperitoneal injection of PLGA [Poly(D-L-lactide-co-glycolic) acid] particles - Myren, Stine Mari (Universitetet i Tromsø, 2007)
Vaccines in aquaculture are heading into the 21st century facing old challenges with new possibilities. Fish die each year as a result of inefficient vaccination against intracellular pathogens e.g. infectious pancreatic necrosis virus (IPNV). A successful prophylactic strategy to combat viral diseases like IPN in fish farming depend both on innate immune responses, like cytokines and natural killer cells, and on specific responses, like antibodies and cytotoxic T cells. In new vaccine strategies for fish, knowledge of how to effective stimulate innate immune responses is essential. In this study we have investigated the expression of pro-inflammatory cytokines after injection of empty fluorescent Poly(D-L-lactide-co-glycolic) acid particles (PLGA) to see what affect PLGA particles have on the immune response per se. Four groups of Atlantic salmon of ~80 g were intraperitoneally injected with respectively NaCl (0.9%), LPS (1mg/kg), PLGA (108 particles/fish) and a mixture of PLGA (108 particles/fish)/LPS (1mg/kg). Tissue and cell samples were collected at day 2, 4, 7, 14 and 30 post-injection. Cell samples were taken from head kidney and peritoneum, and tissue samples from liver and spleen. The expression of the pro-inflammatory cytokines, IL-1b, IL-6, IL-8 and TNF-α1 in peritoneum, spleen, liver and head kidney macrophages was measured using Real time Reverse transcriptase Polymerase chain reaction (Real-time RT-PCR). In head kidney macrophages and peritoneum the expression levels in the 3 experimental groups, injected with PLGA, LPS and a PLGA/LPS mix were low throughout the whole sampling period. Expression of IL-6 in liver was too low to be detected in all 3 experimental groups and also in the saline injected fish. The results from spleen and liver of fish injected with PLGA/LPS and LPS showed elevated levels of especially TNF-α1, IL-6 and IL-8 at early stages (2-4 days), and overall elevated mRNA transcript levels were detected at early stages. The particles were labelled with 6-coumarin, for a visual study ...